Pyridinyl trifluoromethanesulfonates: preparation methods and use in organic synthesis; Russian Chemical Bulletin; Vol. 65, iss. 2 - Kasanova A. Zh. Asiya Zhursunovna; Krasnokutskaya E. A . Elena Aleksandrovna; Filimonov V. D. Viktor Dmitrievich (2016, 2016)
Title screen